A Cross-Sectional Study to Assess Awareness and Practices Related to Prevention of COVID-19 amongst Shopkeepers near Medical Establishments - Shruti Shastri; Dinesh Bhatnagar (National Journal of Community Medicine, 2021)
Background: The World is experiencing Corona virus Disease 2019(COVID-19) pandemic. Respiratory and hand hygiene prevents COVID-19 infection. Shopkeepers near medical establishments have higher risk of catching and transmitting infection as they cater to patients and attendants. Awareness and practices regarding preventive measures is important for their safety.